2019
DOI: 10.1556/038.54.2019.026
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Root-Knot Nematode Meloidogyne incognita and Weeds in Protected Cucumber with Dimethyl Disulfide (DMDS) over Two Crop Cycles: The First Results in Hungary

Abstract: The effectiveness of dimethyl disulfide (DMDS) to control root-knot nematodes (Meloidogyne spp.) and weeds was tested for the first time in Hungary in two consecutive protected cucumber crops with application made only before the first crop. The treatments were Accolade EC (DMDS 94.1%) at 400 l/ha applied by driplines, Nemathorin 10 G (fosthiazate) at 30 kg/ha, and an untreated control. During the first cucumber cycle vigour-index, yield, root-gall index, Meloidogyne juveniles in the soil and germination of we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
(38 reference statements)
1
5
0
Order By: Relevance
“…Information on the long-lasting effects of one fumigation treatment in more successive crops is also useful for economical and practical agronomic decisions. Our study clearly demonstrates the effectivity of DMDS alone and in strategies of over two-three crop cycles per year, confirming the previous results of Toth et al [20].…”
Section: Discussionsupporting
confidence: 92%
“…Information on the long-lasting effects of one fumigation treatment in more successive crops is also useful for economical and practical agronomic decisions. Our study clearly demonstrates the effectivity of DMDS alone and in strategies of over two-three crop cycles per year, confirming the previous results of Toth et al [20].…”
Section: Discussionsupporting
confidence: 92%
“…It revealed that time duration after application of fosthiazate reduced the drug efficacy against rook-knot nematodes. Previous studies also revealed decrease in root-knot index in fosthiazate treated plants (Landi et al, 2018;Toth et al, 2019). Further, the disease severity (grade 1-9) was higher in MCK than MF but fruit yield of Cucumis melo var.…”
Section: Discussionmentioning
confidence: 76%
“…Currently, many chemical nematicides are used to control root-knot nematodes. In preceding reports, fosthiazate has been used to control root-knot disease in cucumber resulting in a reduced root-gall index and increased crop yield in the nematicide treatment group compared with the untreated control group (Toth et al, 2019). Further, fosthiazate in combination with other nematicides has reduced root galling activity of Meloidogyne icognita and also increased tomato yield (Landi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In order to verify the speculation that the nematicidal VOCs are the primary nematicidal toxin of strain MCCC 1K02966, four VOCs produced by B. aryabhattai MCCC 1K02966 were purchased ( Table 1 ). Among these VOCs, dimethyl disulfide has been reported to have nematicidal activity [ 28 , 29 , 30 ], this research focused on the nematicidal activity of pentane, 1-butanol, and methyl thioacetate. Second-stage juveniles (J2s) were immersed in these VOCs at various concentrations to detect contact nematicidal activity against M. incognita .…”
Section: Resultsmentioning
confidence: 99%
“…Dimethyl disulfide has contact and fumigant activity against root-knot nematodes [ 28 ] and an attractive activity on them [ 35 ]. Moreover, dimethyl disulfide as a fumigant was effective against root-knot nematodes in greenhouse and field experiments [ 29 , 30 , 34 ]. Therefore, we purchased the commercial products of the other three VOCs for bioassay.…”
Section: Discussionmentioning
confidence: 99%